Efficacy and safety of a double-coated paclitaxel-eluting coronary stent: The EUCATAX trial - Rodriguez, Alfredo E. (2011)
Objectives: The aim of this study was the comparison of a new double-coated paclitaxel-eluting coronary stent with bare-metal stent (BMS) in patients undergoing percutaneous coronary intervention. Background: Stent coating with biodegradable polymers as a platform for elution of drugs has the potential for complete elution of drugs and for decreasing the risk of late complications. Methods: Multicenter randomized trial comparing a paclitaxel-eluting stent (PES) coated with a biodegradable polymer and glycocalyx with the equivalent BMS. We randomly assigned 422 patients with de novo coronary lesions to PES (211 patients) or to BMS (211 patients). Primary end point was target vessel failure (TVF) defined as cardiac death, myocardial infarction, and target vessel revascularization. Clinical secondary end points were target vessel revascularization, target lesion revascularization, stent thrombosis (ST), and major adverse cardiovascular events (MACE). Angiographic secondary end points were late loss and binary restenosis. Results: At 1 year of follow-up, TVF rate was 9.5% in the PES group and 17.1% in the BMS group (P = 0.02), and MACE rate was 10% in PES and 19% in BMS arm (P = 0.009). All other secondary end points were reached but ST. ST rate was low and similar in both study arms. Conclusions: The study shows that patients treated with PES with dual coating technology had significantly lower incidence of TVF and MACE than those treated with BMS design; however, longer follow-up should be necessary to assess true advantages of this technology compared with the previous one.